Pengaruh In-the-Job Training Dan Off-the-Job Training Terhadap Peningkatan Kinerja Guru Pendidikan Anak Usia Dini: The Influence of In-the-Job Training and Off-the-Job Training on Improving the Performance of Early Childhood Education Teachers - Vera Firdaus; Hisbiyatul Hasanah (Fenomena, 2017)
The quality of education in Indonesia remains a serious concern, particularly due to the low performance of teachers, which directly impacts national competitiveness and human resource development. This study is grounded in human resource management theory, specifically training and development, which emphasizes the role of structured job training to enhance employee performance. The research aims to examine the influence of in-the-job training and off-the-job training on improving the performance of early childhood education teachers in Sumbersari, Jember. A quantitative pre-experimental design with a one-group pretest-posttest method was employed. The sample consisted of 50 teachers selected through purposive sampling from the PAUD teacher working group in Sumbersari District. Data were analyzed using a paired sample t-test. The results showed a significant difference in teacher performance before and after the training intervention, with the mean score increasing from 69.56 to 77.42, and a Sig. (2-tailed) value of 0.000 < 0.05. It is concluded that both in-the-job and off-the-job training effectively improve teacher performance. It is recommended that educational institutions regularly integrate such training models into professional development programs to sustain teacher competency enhancement. Kualitas pendidikan di Indonesia masih menjadi perhatian serius, terutama karena rendahnya kinerja guru yang berdampak langsung pada daya saing bangsa dan pengembangan sumber daya manusia. Penelitian ini berlandaskan pada teori manajemen sumber daya manusia, khususnya pelatihan dan pengembangan, yang menekankan pentingnya pelatihan kerja terstruktur untuk meningkatkan kinerja karyawan. Penelitian bertujuan menguji pengaruh pelatihan in the job dan off the job terhadap peningkatan kinerja guru PAUD di Kecamatan Sumbersari, Jember. Metode yang digunakan adalah kuantitatif dengan desain pre-eksperimen one-group pretest-posttest. Sampel sebanyak 50 guru dipilih melalui purposive sampling dari anggota KKG PAUD Kecamatan Sumbersari. Analisis data menggunakan uji t sampel berpasangan. Hasil penelitian menunjukkan terdapat perbedaan signifikan kinerja guru sebelum dan sesudah pelatihan, dengan nilai rata-rata meningkat dari 69,56 menjadi 77,42, serta nilai Sig. (2-tailed) 0,000 < 0,05. Kesimpulannya, pelatihan in the job dan off the job terbukti efektif meningkatkan kinerja guru. Direkomendasikan agar institusi pendidikan secara rutin mengintegrasikan model pelatihan tersebut ke dalam program pengembangan profesional guna menjaga peningkatan kompetensi guru secara berkelanjutan.